Predictors of left ventricle aneurism development in patients with acute anterior Q-wave myocardial infarction - V.D. Syvolap; S.M. Kyselov (Zaporozhye State Medical University, 2013)
67 patients with diagnosis: Q-wave myocardial infarction - were examined. Peculiarities of ECG and echocardiographic indexes were studied depending on the presence of left ventricle aneurism. Predictors of left ventricle aneurism formation were revealed in patients with acute Q-wave myocardial infarction.